Talking and testing : discourse approaches to the assessment of oral proficiency - Young, Richard, 1948-; He, Agnes Weiyun (Studies in bilingualism, 1998)
This book brings together a collection of current research on the assessment of oral proficiency in a second language. Fourteen chapters focus on the use of the language proficiency interview or LPI to assess oral proficiency. The volume addresses the central issue of validity in proficiency assessment: the ways in which the language proficiency interview is accomplished through discourse. Contributors draw on a variety of discourse perspectives, including the ethnography of speaking, conversation analysis, language socialization theory, sociolinguistic variation theory, human interaction resea.